Circle of Culture and permanent education for transformation of professional practice: an integrative review - Rozal, Juliana Ferreira; Monteiro, Estela Maria Leite Meirelles; Marinus, Maria Wanderleya de Lavor Coriolano; Santos, Tamyris Arcoverde (Ciência & saude coletiva, 2023)
This article aimed to know the scientific evidence that underlies Culture Circle application as a device of Permanent Education in Health for professional practice transformation. This is an integrative literature review carried out in the PubMed, CINAHL, LILACS and Scopus databases, in October 2021, with the descriptors "health professionals", "professional practice", "continuing education", "health promotion" and the uncontrolled term "Culture Circle". Data were analyzed in a descriptive way. The results identified 217 articles and five were included to compose the final sample. It was identified that the most discussed themes in Culture Circles were health education and health promotion. There was an average of 13 participants, lasting between one and a half to four hours, with the presence of an animator/researcher and carried out in the workplace. It is concluded that applying Culture Circles in Permanent Education in Health is a powerful inducer of change in professional practice. Recommendations are presented for its application in empowering subjects and in strengthening health promotion actions as well as the need for field research to broaden the understanding of the implication of the method and its consequences in professional practice.This article aimed to know the scientific evidence that underlies Culture Circle application as a device of Permanent Education in Health for professional practice transformation. This is an integrative literature review carried out in the PubMed, CINAHL, LILACS and Scopus databases, in October 2021, with the descriptors "health professionals", "professional practice", "continuing education", "health promotion" and the uncontrolled term "Culture Circle". Data were analyzed in a descriptive way. The results identified 217 articles and five were included to compose the final sample. It was identified that the most discussed themes in Culture Circles were health education and health promotion. There was an average of 13 participants, lasting between one and a half to four hours, with the presence of an animator/researcher and carried out in the workplace. It is concluded that applying Culture Circles in Permanent Education in Health is a powerful inducer of change in professional practice. Recommendations are presented for its application in empowering subjects and in strengthening health promotion actions as well as the need for field research to broaden the understanding of the implication of the method and its consequences in professional practice.